Komunikacja „cyfrowych tubylców” za pośrednictwem telefonu komórkowego - Joanna Dziekońska (Problemy Wczesnej Edukacji)
The article presents the contemporary young generation of so-called digital natives who are growing up in the age of remix. This untypical sphere is based on an inseparable, mutually complementing and mixed relation between the new media and culture. Remix, like every novelty, displays ambivalent implications and, as a consequence, becomes a challenge for contemporary researchers who analyse social reality. The study of children functioning within the new media is of the highest priority because of creating and maintaining relations with the digital natives – otherwise, the gap between them and the digital immigrants deepens that which destructively influences the educational process. Considering the above, the communicative experiences of children functioning in the world of remix become the subject of research conducted in the present article. The aim of the research was to advance the knowledge of how primary school third-formers communicate via the mobile phone, which is one of the most popular new media.